A New Ceramide from Cissus Aralioides Baker (Vitaceae) and its Antimicrobial Activity. Issue 1 (16th December 2022) - Nago, Romeo Desire T.; Simo Mpetga, James D.; Tamokou, Jean‐De‐Dieu; Tanemossu Fobofou, Serge A.; Mbahbou Bitchagno, Gabin T.; Wessjohann, Ludger A.; Tene, Mathieu; Silvere Ngouela, Augustin
Abstract: Purification through repeated column chromatography over silica gel and Sephadex LH‐20 of the ethanol extract of the stems of Cissus aralioides (Baker) Planch. resulted in the isolation of a new ceramide, aralioidamide A (1 ), along with five known compounds (2–6 ). Their structures were determined by the extensive analyses of their spectroscopic (1D and 2D NMR) and spectrometric data, and comparison with those reported in the literature. Aralioidamide A (1 ) displayed weak antibacterial activity (MIC=256 μg/mL) against Bacillus subtilis, Staphylococcus aureus and Shigella flexneri and was inactive (MIC>256 μg/mL) against the tested fungi. Abstract :